Hubungan Antara Kecerdasan Emosional Dengan Prestasi Belajar Siswa Dalam Mata Pelajaran Matematika Kelas VI Sekolah Dasar: Relationship Between Emotional Intelligence With Student Learning Achievement In Mathematics Subjects Class VI Elementary School - Priharyanti, Rifani (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the relationship between emotional intelligence and mathematics learning achievement in grade VI students of SDN Harjasari 1. Using the correlational survey method, the study was conducted on 32 students selected through simple random sampling technique. Emotional intelligence was measured using a Likert scale questionnaire developed based on Goleman's theory, while mathematics learning achievement was obtained from documentation of final semester grades. The results showed a significant positive relationship between emotional intelligence and math learning achievement with a correlation coefficient of 0.873 and a coefficient of determination of 76.21%. The regression equation obtained is Ŷ = 10.513 + 0.593X, indicating that every one unit increase in emotional intelligence will increase math learning achievement by 0.593 units. This finding confirms that in math learning, which is often considered complex, emotional intelligence plays an important role in helping students overcome learning challenges and difficulties, thereby improving their academic performance.